STUDI LITERATUR: IMPLEMENTASI PENDIDIKAN KARAKTER SISWA SEKOLAH DASAR DI ERA NEW NORMAL - Mirda Indriani; Alisia Rahmadini; Dwi Inda Kurnianti (Jurnal PAJAR (Pendidikan dan Pengajaran), 2022)
Character education is essential for every student, both within educational settings and daily life, to develop the foundation for a quality national character. Character is closely linked to social values and norms. In the new normal era, humans have begun to adapt to various changes; however, the use of social media and the internet remains a concern, particularly for elementary school students engaged in online learning. Therefore, students require appropriate character education and effective socialization methods. This study employs a literature review method, synthesizing existing theories and research into a relevant framework. The results indicate that the implementation of character education in elementary schools during the pandemic was effective, supported by teachers, schools, and parental contributions. Researchers recommend that future studies adapt methods to the specific context and needs of each school.